Multifunctional hybrid structures made of open-cell aluminum foam impregnated with cellulose/graphene nanocomposites. (15th June 2020) - Pinto, Susana C.; Silva, Nuno H.C.S.; Pinto, Ricardo J.B.; Freire, Carmen S.R.; Duarte, Isabel; Vicente, Romeu; Vesenjak, Matej; Marques, Paula A.A.P.
Highlights: Foams based on disintegrated BC, GBMs and PCMs were prepared by freeze-drying; Enhanced foams dimensional stability and fire-retardancy were due to GBMs presence; Foams showed hydrophobic character after being exposed to MTMS vapour; Hybrid structures of Al-OC impregnated with optimized foam (Al-BC/GO) were prepared; Al-BC/GO had higher mechanical, sound absorption ability and low thermal conductivity. Abstract: This work focuses on exploring combinations of disintegrated bacterial cellulose nanofibres (BC) with graphene oxide (GO) (reduced and non-reduced) and phase change materials (PCMs) prepared in the form of foam-like structures. The presence of GO remarkable improves the fire-retardancy and provides dimensional stability to the foams while PCMs gives thermal energy storage capacity. The foams were exposed to methyltrimethoxysilane (MTMS) vapour to become hydrophobic which was confirmed by measuring water absorption capacity and water contact angle. To extend the multifunctionality of these nanocomposite foams, a selected composition was impregnated into an open-cell aluminium foam creating a hybrid structure (Al-BC/GO) with higher mechanical properties (increase in stress of 100 times) and high sound absorption coefficient (near 1 between 1000-4000 Hz). The low thermal conductivity confirms that this hybrid structure is a thermal insulator. These advantages highlight the potential applications of the proposed materials e.g. construction, automotive and aeronautical sectors.